2011
DOI: 10.1136/annrheumdis-2011-200245
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial mutagenesis correlates with the local inflammatory environment in arthritis

Abstract: High mitochondrial mutations are strongly associated with synovial inflammation showing a direct link between mitochondrial mutations and key proinflammatory pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 42 publications
(50 reference statements)
4
55
0
Order By: Relevance
“…We studied the regulation of SIRT1 protein in vivo and found that SIRT1 levels were up regulated in the synovial tissues of RA smokers and correlated positively with increased leukocytic infiltration. Previously, it was shown that smokers respond less to therapies with disease modifying anti-rheumatic drugs and had higher levels of the chemokine MIP-1α [35]. The same study showed that CSE induces chemotaxis in vitro.…”
Section: Discussionsupporting
confidence: 50%
“…We studied the regulation of SIRT1 protein in vivo and found that SIRT1 levels were up regulated in the synovial tissues of RA smokers and correlated positively with increased leukocytic infiltration. Previously, it was shown that smokers respond less to therapies with disease modifying anti-rheumatic drugs and had higher levels of the chemokine MIP-1α [35]. The same study showed that CSE induces chemotaxis in vitro.…”
Section: Discussionsupporting
confidence: 50%
“…28 This quantitative PCR-based approach enables precise determination of mutation frequencies following exhaustive digestion of all wild type (non-mutant) sequences by the restriction enzyme Taq-I. Mitochondrial DNA was extracted using a previously reported protocol.…”
Section: Mitochondrial Random Mutation Capture Assaymentioning
confidence: 99%
“…Mitochondrial DNA was extracted using a previously reported protocol. 28 Following extraction, 10 μg of mtDNA was digested with 100 units of Taq αI restriction enzyme (New England Biolabs), 1× bovine serum albumin and a Taq αI-specific digestion buffer (10 mM Tris HCl, 10 mM MgCl 2 , 100 mM NaCl ( pH 8.4)) for 10 h, with 100 units of Taq-αI added to the reaction mixture every hour. PCR amplification was performed in 25 μL reaction mixtures containing 12.5 μL 2×SYBR Green Brilliant Mastermix (Stratagene), 0.1 μL uracil DNA glycosylase (New England Biolabs), 0.7 μL forward and reverse primers (10 pM/μL; DNA oligonucleotide (IDT)) and 6.7 μL H 2 O.…”
Section: Mitochondrial Random Mutation Capture Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mitochondrial dysfunction contributes to cell growth, tumorigenesis and inhibition of apoptosis and it is not surprising that key oncogenes and tumor suppressors modulate mitochondrial dynamics through important signaling pathways. [6][7][8][9][10] Other mitochondria-related diseases include a number of genetic or acquired diseases, such as diabetes, 11 cardiologic, 12 vascular 13 and haematologic diseases, 14 15 Parkinson's disease, 16 Alzheimer's disease, 17 amyotrophic lateral sclerosis, 18 multiple sclerosis, 19 20 epilepsy, 21 22 and autistic spectrum disorders, 23 24 ataxia-telangiectasia, [25][26][27] Bloom syndrome, 28 29 Down syndrome, 30-32 psoriasis 33 34 and rheumatoid arthritis, [36][37][38] Due to the unmet demand for mitochondrial diseases, increasing interest in mitochondria-specific targeting has lead to the emergence of "Mitochondrial Medicine" as a new field of biomedical research.…”
Section: Introductionmentioning
confidence: 99%